Efektivitas Penggunaan Sistem Informasi Akuntansi, Kepercayaan atas Sistem Informasi Akuntansi, dan Kesesuaian Tugas terhadap Kinerja Individu pada Bank Perkreditan Rakyat (BPR) - Saraswati, Esti; Bangun Kristianto, Giovanny; Yuliarti, Lusi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The objective of this study is to investigate and evaluate the effect of the effectiveness of utilizing Accounting Information System (AIS), trust in the AIS and suitability of tasks on the performance of individuals working at rural banks through simultaneous and partial tests. In this study, 32 individuals who worked at PT Bank Perkreditan Rakyat (BPR) Soka Panca Artha in Sokaraja, Banyumas, were included in the population. The study utilized various stages of research methodology, which included performing descriptive statistical analysis, testing the quality of data, evaluating classical assumptions, conducting multiple regression analysis, and testing hypotheses. The data was primary data collected by distributing questionnaires. Â The findings of this study suggested that the effectiveness of AIS use, trust in AIS, and task suitability greatly influences individual performance simultaneously. The partial testing conducted indicated that the use of AIS and the level of trust in AIS did not significantly affect individual performance. However, the suitability of the task had a significant impact on individual performance